Global Warming and the Political Ecology of Health: Emerging Crisis and Systemic Solutions - Kate Smith (Ethnobiology Letters, 2012)
Review of Global Warming and the Political Ecology of Health: Emerging Crisis and Systemic Solutions. Hans Baer and Merrill Singer. 2008. Left Coast Press, Inc., Walnut Creek, CA. Pp. 238. $32.95 (paperback). ISBN 978-1-59874-354-8.